Strategic Management of Learning Facilities and Infrastructure in Developing Fashion Expertise Competency at SMK Negeri 6 Garut Regency - Winna Islamiyathi; R. Supyan Sauri (CV. Media Digital Publikasi Indonesia, 2026)
This research addresses critical challenges in managing facilities and infrastructure within Vocational High School (SMK) Fashion Expertise programs, such as limited budgets, poor maintenance, and a disconnect from current fashion industry technology. Effective strategic management is crucial for SMKs to produce competent, work-ready graduates. This study aimed to describe the strategic management of learning facilities implemented to enhance fashion competency at SMKN 6 Garut Regency. A qualitative case study design utilized data from observation, interviews, and documentation. The findings indicate that the school effectively implemented strategic management principles, encompassing environmental analysis, strategy formulation, implementation (including the Teaching Factory model), and rigorous evaluation. This systematic approach ensured that the school’s facilities were complete, well-maintained, and integrated into practical learning programs. The successful implementation significantly improved student competency and industry alignment. The study recommends continuous staff training and strengthening collaboration with industry partners to keep facilities updated with the rapid advancements in fashion technology.